Optimization of Construction Parameters and Deformation Characteristics of Large-Section Loess Tunnel: A Case Study from Xi’an Metro - Mingji Zhao; Yun Cheng; Zhanping Song; Tong Wang; Yuwei Zhang; Baichao Liulian (Advances in Civil Engineering)
Loess geological tunnels are characterized by weak geological structure and poor self-stability of surrounding rock, so effectively controlling the excavation face distances of different caverns is of great significance for guiding the safe construction of large-section tunnels. Based on the excavation of large-section loess tunnel from Xi’an Metro Line 4, the optimal excavation face distance is determined based on Midas numerical model. Then, the surface settlement and horizontal deformation are analyzed based on monitoring data, and, finally, the rationality of excavation face distance is verified. The results show that the influence of excavation face distance on surface settlement, vault settlement, and horizontal deformation is consistent. The surface settlement mainly occurs in the range of −20∼20 m from the tunnel centerline and the settlement trough formed has asymmetric characteristics. The vault settlement and horizontal deformation undergo first a rapid settlement and then a slow settlement. The connection between initial support and middle partition is mainly tensile stress and the middle and bottom parts of the supporting structure are mainly compressive stress. Numerical results suggest that the optimal excavation faces distance of L1, L2, and L3 which can be 4, 9, and 9 m, respectively. Construction monitoring data show that the double-sides heading method has a significant effect on surface settlement, vault settlement, and horizontal deformation. The surface settlement occurs within the range of −17∼6 m from the tunnel centerline. The maximum vault settlement and horizontal deformation are 73.00% and 65.50% of the maximum allowable. It can be seen that the actual excavation parameters optimized by Midas numerical model have high reliability.